Wishtress - Brandes, Nadine, 1986- (Nashville, Tennessee : Thomas Nelson, 2022)
Myrthe, a girl who can create wishes, teams up with Bastiaan, a boy who can stop time, to break a curse that will bring on her death with the next tear she sheds.
Map by Matthew Covington and Autumn Short.
"Include discussion questions"--Page 4 of dust jacket.
Keywords: Ability -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Fantasy fiction; Novels